2008
DOI: 10.1016/j.joca.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in articular cartilage of rat knee joints after spinal cord injury

Abstract: Cartilage alterations after SCI would not be explained by only a suppression of mechanical forces by unloading and immobilization, but there may be influences on the cartilage in addition to the change in mechanical forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 33 publications
(32 reference statements)
2
43
1
Order By: Relevance
“…The results of these animal studies have indicated that changes during immobilization may differ between different cartilage plates of the knee, 10 and showed different patterns of alterations between the superficial and deep cartilage, based on the different mechanical conditions specific for each site. 11 Taken together, we have previously verified the influence of mechanical forces on the articular cartilage after SCI and proposed that cartilage alterations would not be explained by only a suppression of mechanical forces; 9 however, because of the high interregion variability in morphologic cartilage properties, a previous experiment in only the medial knee cartilage did not allow us to reliably negate the influence of mechanical forces.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The results of these animal studies have indicated that changes during immobilization may differ between different cartilage plates of the knee, 10 and showed different patterns of alterations between the superficial and deep cartilage, based on the different mechanical conditions specific for each site. 11 Taken together, we have previously verified the influence of mechanical forces on the articular cartilage after SCI and proposed that cartilage alterations would not be explained by only a suppression of mechanical forces; 9 however, because of the high interregion variability in morphologic cartilage properties, a previous experiment in only the medial knee cartilage did not allow us to reliably negate the influence of mechanical forces.…”
Section: Introductionmentioning
confidence: 83%
“…[5][6][7]9 The eight SCI animals were anesthetized by intraperitoneal administration of 40 mg kg À1 sodium pentobarbital. After the spinal cord was exposed by a laminectomy of the T8 vertebra, it was completely transected at the level of T8.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations